PRAGMATIC FEATURES OF ANTITHESIS IN UZBEK AND ENGLISH LITERARY TEXTS - Raximovna, Ruzibaeva Nigorakhon; Mirusmanovna, Mirgiyazova Munisa (International Journal of Psychosocial Rehabilitation, 2020)
The article deals with the pragmatic analysis of the stylistic device, antithesis on the basis of literary texts in English and Uzbek languages. It can be said that pragmatics is the semantics of language in action and the totality of conditions that accompany the use of a language sign. Antithesis is a stylistic device that is created by presenting opposite meaning words. Its provision is mostly seen in literary texts and the texts of fictions are of high importance to investigate thoroughly. The article provides the comparative analysis of the usage of antithesis and its pragmatic aspect by means of the extracts taken by English and Uzbek literary texts.